The VACStent trial: combined treatment of esophageal leaks by covered stent and endoscopic vacuum therapy - Lange, Jonas; Kähler, Georg; Bernhardt, J.; Knievel, J.; Dormann, A.; Hügle, U.; Eisenberger, C. F.; Heiss, M. M. (Surgical endoscopy and other interventional techniques, 2023)
Endoscopic treatment of esophageal leaks, mostly by covered stents or endoscopic vacuum therapy (EVT), has largely improved the clinical outcome in the last decade. However, both techniques suffer from significant limitations. Covered stents are hampered by a high rate of migration and missing functional drainage, whereas endoluminal EVT devices are limited by obstruction of the GI tract. The new design of the VACStent makes it a fully covered stent within a polyurethane sponge cylinder, allowing EVT while stent passage is still open. Initial clinical applications have demonstrated the fundamental concept of the VACStent.